Adubação fosfatada para a cultura do sorgo granífero - Silva Cruz, Sihelio Julio; de Oliveira, Sanielle Costa; Silva Cruz, Simerio Carlos [UNESP]; Machado, Carla Gomes [UNESP]; Pereira, Rodrigo Gomes (Univ Fed Rural Semi-arido-ufersa, 2009)
The objective of this work was to evaluate the influence of crescents phosphorus levels in two hybrids of forage sorghum cultivated on "Zona da Mata" region, State of Alagoas. The treatments were two hybrids of forage sorghum: BRS304 e BRS310, and four phosphorus levels: 0, 25, 50 e 75 kg ha(-1). The statistical design was the complete randomized block with four replications in a split plot scheme. Each experimental plot was constuited for five row of 4.5 m, spaced of 0.70 m. The soil of experimental area received lime to increase basis saturation to 60%. During the sowing, all experimental area received 100 and 120 kg ha(-1) of N and K, respectively. The plants were collected 40, 50, 60 e 70 days after emergence. The mass collected was separaeted in leaves photosynthetic active and remaining of the plant. When the grains were on the "farinaceo duro" stage, the yield was evaluated in 1.4 m(2) on plots center. The phosphoted fertilization increases linearly the sorghum production until 75 kg ha(-1) level of P. The phosphorus provides better grain participation on total dry matter of sorghum plants.

Objetivou-se, neste trabalho, avaliar a resposta de dois híbridos de sorgo granífero a doses crescentes de fósforo cultivados na região da Zona da Mata do Estado de Alagoas. Os tratamentos foram constituídos por dois híbridos de sorgo granífero: BRS304 e BRS310, e quatro doses de fósforo: 0, 25, 50 e 75 kg ha-1, dispostos em blocos casualisados com quatro repetições em esquema de parcelas subdivididas. Cada parcela experimental foi formada por cinco fileiras de 4,5 m de comprimento, espaçadas de 0,70 m. O solo da área experimental recebeu calagem para elevar a saturação por bases a 60%. Foram adotados os níveis de adubação de 100 e 120 kg ha-1 para o N e K, respectivamente. O sorgo foi semeado manualmente estabelecendo-se uma densidade populacional de 160.000 plantas ha-1. Amostragens de plantas foram coletadas aos 40, 50, 60 e 70 dias após a emergência. A biomassa coletada foi separada em folhas fotossinteticamente ativas e no restante da planta. Quando os grãos se apresentavam no estádio farináceo duro avaliou-se a produtividade amostrando-se áreas de 1,4 m2 no centro das parcelas. A adubação fosfatada aumenta linearmente a produção de sorgo até a dose de 75 kg ha-1 de P. O fósforo proporciona maior participação de grãos na matéria seca total das plantas de sorgo.
Phosphate fertilization for forage sorghum crop
Keywords: Sorghum bicolor L. Moench; grain yield; phosphorus doses